An Efficacy of Cartoon Videos on Reducing Pain in Infants during Vaccination - Jadhav, Pratibha (Indian Journal of Nursing Sciences, 2024)
Background: A majority of these injections are administered in the early periods of infancy. Uncontrolled pain experienced in early periods of life has a negative and long-lasting effect such as distress and can negatively affect the development of the central nervous system. Distraction is a method that increases pain tolerance by drawing attention away from the painful stimulus to other directions and is considered a powerful means of pain management in children. Aim: The aim of the study was to assess the pain perception during vaccination among infants in the experimental and control group and to compare pain perception among infants in the experimental and control group . Materials and Methods: This study was based on quasi-experimental research approach. The researchers used one group pre-test-post-test research design for the study. Non-probability convenient sampling technique was used to select 60 samples for the study in selected hospitals of Navi Mumbai. Structured questionnaire and Neonatal Infant Pain Scale were used for the data collection. Results: In control group, 60% of female and 40% of male infants and in experiment group, 50% of male and 50% of female infants wear present. Overall, mean pain score in the experimental group is 3.6333 and mean pain score in the control group is 5.7000. It is proven that cartoon videos are effective in reducing pain in infants during vaccination. Conclusion: This study concluded that cartoon videos are effective distraction strategy to reduce pain and distress among children during intramuscular injections. We can use same technique as a nursing intervention while giving care to children’s in pediatric departments.